(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This study aimed to determine the effect of the type of milk on the chemical properties, textural properties, and separation percentage of cheddar cheese produced from cow’s milk and goat’s milk. Where cheddar cheese is made from T1-modified cow’s milk. Cheddar cheese is also made from T2 modified fat goat milk. The cheese was kept in ripening rooms at a temperature of 13°C for 6 months, and tests were conducted on the treatments during 1, 60, 120, and 180 days of the ripening period. The chemical tests included estimating the percentage of moisture, protein, fat, ash, carbohydrates, and total acidity, in addition to estimating the acidity. pH, while rheological tests included hardness, cohesion and flexibility. The percentage of purification of the cheddar cheese treatments was also estimated. The results showed that the cheddar cheese produced from goat’s milk was characterized by a lower moisture content than the cheddar cheese produced from cow’s milk. The percentages of protein, fat, ash, and acidity also increased, while the percentage of carbohydrates and PH decreased in the cheddar cheese produced from goat’s milk compared to Cheddar cheese produced from cow’s milk. The results of rheological tests also showed lower values of hardness and cohesion and higher elasticity in cheddar cheese produced from goat’s milk compared to cheddar cheese produced from cow’s milk. The results also showed a lower percentage of decantation in cheddar cheese produced from goat’s milk compared to cheddar cheese produced from cow’s milk